Implicación taxonómica de estudios morfológicos comparativos en Blechnum L. (Blechnaceae – Pteridophyta) - Lavalle, María Del Carmen; Gardella, María Cristina; Cortizo, Lorena; Bodnar, Josefina; Rodríguez, Mónica (Botanica Complutensis, 2007)
Four species of the genus Blechnum are comparatively studied with the goal of updating the taxonomy and contributing new data to the understanding of the genus. The taxa studied are: B. asplenioides Sw., B. blechnoides (Lag. ex Sw.) C. Chr., B. polypodioides Raddi and B. unilaterale Sw. The characters selected for this study were: architecture of fronds, morphology of the indument of laminae and axis, epidermal patterns, adult stomata and spores. The analysis of these features provided evidence in favor of considering that these four species are cospecific.